LAUDATIO. PROFESSOR COSTEL SÂRBU ON HIS 65ᵀᴴ ANNIVERSARY - COBZAC, Simona Codruța Aurora; CASONI, Dorina (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Professor Dr. Habil. Costel Sârbu is one of the pioneers of Chemometrics in Romania. He was born on January 12 1951 in Giurgița, Dolj county Romania. He obtained his B.S. degree in 1975 from Babeş-Bolyai University in Cluj-Napoca, followed by his MSc degree in 1976 from the same university. In 1987, he gained the PhD in chemistry with the thesis entitled Applications of Information Theory in Chromatography with Fluorescence Detection, under the scientific supervision of illustrious Professor Candin Liteanu. After a short period of engagement in the industry and research, in 1980, he began his academic career as assistant professor at the Polytechnic Institute in Cluj-Napoca. From 1990 onwards, he continued the academic career as a lecturer (1990-1994), associate professor (1994-2014) and full professor (2014-2016) at the Faculty of Chemistry and Chemical Engineering of Babeş-Bolyai University in Cluj-Napoca. After his retirement in 2016, he was honoured with the position of Professor Emeritus.